(untitled) (Research, Society and Development, 2022)
This research aims to estimate the design costs of implementing the bioconcrete samples suitable for structural purposes. The bioconcrete samples were produced by adding specific bacteria, Sporosarcina pasteurii. The specimens were submitted to tests of resistance to axial compression according to ABNT NBR 5739 under water-curing periods of 7, 14, and 28 days. To the implementation of this research, it was necessary execution of some stages: bibliographic research, and the providing of better visualization of the theme. The initial acquisition of bacteria, then the cultivation of bacteria to incorporate in the concrete. The third stage was laboratory tests to analyze the new concrete and make reports and data tabulation. The early costs results are encouraging further study.